Feasibility Analysis of Freshwater Fish Farming Business at Karya Mulya Fish Farming Group, Banyumas Regency - Mustika Palupi; Ren Fitriadi; Muhamad Sulaiman Dadiono; Rika Prihati Cahyaning Pertiwi; Candro Dea Bagaskara Super Yudhistira (Department of Aquaculture, 2021)
This study aims to determine the feasibility of freshwater fish farming as an effort to support the minapolitan area of the Banyumas Regency. The research was carried out in Karang Lewas District. Data collection was carried out proportionally by interviewing the fish farmers of each fish farming group. Data analysis on the feasibility of fish farming was performed using the B/C ratio, PP, and BEP (Break-Even Point) criteria. The analysis method of the business feasibility was an analysis of business costs and income. Results of the analysis of B/C ratio value in fish farming was 1.13 to 1.69, BEP calculation used data according to the respondents, while the Payback Period (PP) of the fish farming ranged between 1.00-1.49 meaning that the capital return in less than 5 years. Those values state that the activities of freshwater fish farming have a capital return of more or less over 1 - 1.5 years. It shows that the business of freshwater fish farming in both hatcheries and fish rearing is feasible to maintain.